Nutritional status of patients with tuberculosis attending at tertiary medical center in Bangladesh - Rahaman, Mohammad Ferdous Ur; Shefa, Jannatara; Mandal, Manos Kumar; Alam, Md Rafiqul (Bangladesh Journal of Medicine, 2019)
Background: Tuberculosis (TB) is a common communicable disease in Bangladesh. Treatment of TB sometimes depends on nutritional status of the patient. Both in developed and developing countries TB has been found to coexist with malnutrition among patients at the beginning of treatment. So it would be very important to evaluate the nutritional assessment of a patient before starting treatment. If malnutrition exists in a patient of TB than nutrition supplementation can play an important role in improving the disease condition to reduce further morbidity and mortality. Method:It was a descriptive study, conducted on eighty-seven adult TB participant attending at medicine department, Bangabandhu Sheikh Mujib Medical University (BSMMU), where nutritional status (Body-Mass Index or BMI) was measured by keeping records of patient’s height in meters and weight in kilogram. Result: A total 87 participants were included in this study where 45 (52 percent) were males and 42 (48 percent) were females. Most of the participants were healthy 56 percent (n=49) participants. However, under-nutrition was present in 36 percent (n=31) participants and over-nutrition were only 8 percent (n=7). Most of the participant takes more than three meals 54 percent (n=47) participants. However, three meals were taken by 45 percent (n=39) participants and two meals were taken only 1 percent (n=1). Conclusion: In this study almost 36% participants of tuberculosis were in under-nutrition. So Nutrition supplementation could be needed in improving the disease condition to reduce further morbidity and mortality. On the other hand large scale study should be needed for taking proper steps to know the overall situation of the country. Bangladesh J Medicine July 2019; 30(2) : 53-57